Haplotype analysis of long-tailed macaques in TNB Bukit Selambau, Peninsular Malaysia, leads to inferences of fissionfusion social structure - Siti Nur Aliah, Mohd Isa; Nor Amna, Abu Hassan; Nur Azimah, Osman; Khairulmunir, Mohamad; Aisah, Md Shukor; Ayuni, Samsul Bahri; Shukor, Md Nor; Kayal Vizi, Karuppannan; Muhammad Abu Bakar, Abdul Latiff; Mohd Ridwan, Abd Rahman; Badrul Munir, Md Zain (Journal of Wildlife and Biodiversity (JWB), Arak University, 2023)
Long-tailed macaques have been roaming near Tenaga National Berhad Bukit Selambau Solar(TBSS) causing human–macaque conflicts. This study reveals the social organization and genetic variation of these macaques. Macaques’ groups were determined via direct observation and closed circuit television. Genomic DNA from 29 fecal samples were extracted and proceeded with amplification of the D-loop region of mitochondrial DNA. There are four main groups of primates at TBSS. Some members of the Kuil group and the Pekan group shared haplotype 1, forming a fission-fusion society. This finding can be used for TNB in mitigation plans involving human– macaque conflict.